Journey to school, safety and security of school children in Benin City, Nigeria (2013)
School children travel forms an important part of the general traffic planning. However, over the years the access needs and transport requirements of the children have been overlooked or neglected. The paper examined the travel characteristics of school children and the challenges they faced en-route school. Both primary and secondary data were used for this work. Using multi-stage sampling, 373 questionnaire were administered to school children in selected secondary schools. The questionnaire were purposely administered in those schools. Secondary data were obtained from relevant organizations. Both descriptive and inferential statistics were used for data analysis. Walking accounted for more than 65% of the mode of transport to school. The main reasons for walking to school were short distance (32.4%) and high cost of transportation (27.4%). Poor driving was the most important challenge school children face en-route school. In terms of safety and security, out of 56 school children involved in road crashes, 5.4% had dislocation while only 1.6% of the school children had experienced kidnapping at one time or the other. Students’ T-test showed a significant difference (p < 0.05) in the use of different modes to school. The paper suggests improved drivers’ enlightenment, provision of mass transit, construction and repair of walkways as well as transport policy that addresses the access needs of the school children.